Etika Komunikasi Masyarakat Madura: Analisis Nilai Tengka dan Pengaruh Globalisasi terhadap Penggunaan Bahasa Ibu - Khoiroh, Anisya Umi; Maimun, Maimun; Sofyan, Achmad (YASIN, 2025)
Studies on communication ethics grounded in Madurese local wisdom, particularly the value of tengka as a normative guide for honor and respect in social interaction, remain relatively limited, even though this phenomenon significantly affects the continuity of cultural identity and communication patterns amid globalization. This study aimed to analyze tengka as the ethical foundation of communication within Madurese society and to examine shifts in the use of the Madurese language, especially its speech levels, under the influence of globalization. The research employed a descriptive qualitative method with an ethnographic approach, involving members of the Madurese linguistic community selected through purposive sampling. Data were collected through in-depth interviews, cultural observation, and literature review, and were analyzed using thematic analysis to identify patterns of meaning and communicative practices associated with tengka. The findings show that the levels of the Madurese language (very refined, refined, and coarse) function as a social mechanism for expressing respect, maintaining harmony, and upholding the value of tengka. However, the dominance of the Indonesian language in public spaces and rapid social change have weakened younger generations’ understanding of speech levels and the value of tengka. These findings reinforce cross-cultural communication ethics theory that emphasizes the importance of local norms in maintaining social relations and affirm that tengka plays a central role in shaping communication ethics in Madurese society, despite facing the challenges of modernization. The study’s implications include strengthening the literature on communication ethics rooted in local culture and providing recommendations for local governments, educational institutions, and cultural communities to enhance the preservation of the Madurese language and the value of tengka through cultural education and language revitalization programs, while also opening avenues for further research on the adaptation of tengka in digital contexts and among younger generations.